Effect of fullerene-like nanoparticles on the tribological properties of industrial lubricants for steel rolling - Kartun, I.M.; Remez, O.A.; Haidai, O.O.; Spaska, O.A.; Yanchenko, O.V.; Pyliavsky, V.S.; Polunkin, Ye.V. (Problems of Tribology, 2022)
The paper shows the results of studying the possibility of using fullerene-like nanoparticles as a lubricating additive in the composition of technological lubricant MT-216 M. The lubricity properties were evaluated on a laboratory rolling mill DUO-180 during cold rolling of strips of steel 08kp. The rolling force, the coefficient of friction in the deformation zone were measured, the values of the elongation coefficient and the parameter reflecting the costs of the rolling force per unit deformation of the metal were calculated